If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -5x) + 9 = 2x + -23 + -8x (4 * 2 + -5x * 2) + 9 = 2x + -23 + -8x (8 + -10x) + 9 = 2x + -23 + -8x Reorder the terms: 8 + 9 + -10x = 2x + -23 + -8x Combine like terms: 8 + 9 = 17 17 + -10x = 2x + -23 + -8x Reorder the terms: 17 + -10x = -23 + 2x + -8x Combine like terms: 2x + -8x = -6x 17 + -10x = -23 + -6x Solving 17 + -10x = -23 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 17 + -10x + 6x = -23 + -6x + 6x Combine like terms: -10x + 6x = -4x 17 + -4x = -23 + -6x + 6x Combine like terms: -6x + 6x = 0 17 + -4x = -23 + 0 17 + -4x = -23 Add '-17' to each side of the equation. 17 + -17 + -4x = -23 + -17 Combine like terms: 17 + -17 = 0 0 + -4x = -23 + -17 -4x = -23 + -17 Combine like terms: -23 + -17 = -40 -4x = -40 Divide each side by '-4'. x = 10 Simplifying x = 10
| 7(6x+7)=91 | | 5+6x=3+5x-8 | | 3x=2x-17.5 | | 2x/5-2x-1/2=x/5 | | 5*6+5x+6x=30x | | 7(8+x)=98 | | 4(x+3)+28=-4x | | -3x-8=5y+32 | | 6x=4y+8 | | (5x-2)(2x+7)= | | 4(y+3)=3y+13 | | 8(7-x)=4(3x-16) | | 8y-6=6y+6 | | 6(3+2x)=54 | | x^2-13x+15=-3x-1 | | 7x+2=12+x | | -16x-20=-13x+55 | | (a+b+c)*(a+b-c)= | | 7x^2+28x-315=0 | | 10=42-2x | | 7x+21=4+2x | | 6(7+2x)=114 | | 2x-3+5x-8=6x+54 | | x^2+4x+10=7 | | x^2+2x=1000 | | 5a-6=3a-8 | | 0=6x^2+5sp-6p^2 | | 8(e-1)=5e+2 | | 3x^2-54x+240=0 | | 6x^2+5sp-6p^2=0 | | 14x+1=21x+4 | | .25x+9=13 |